Hyperglycaemia as a predictor of outcome during non-invasive ventilation in decompensated COPD. Issue 10 (18th May 2009) - Chakrabarti, B; Angus, R M; Agarwal, S; Lane, S; Calverley, P M A
Abstract : Rationale: Hyperglycaemia predicts a poor outcome in Intensive Care Unit (ICU) patients. Whether this is true for respiratory failure necessitating non-invasive ventilation (NIV) is not known. Objectives: To determine whether hyperglycaemia within 24 h of admission independently predicts outcome of NIV during acute decompensated ventilatory failure complicating chronic obstructive pulmonary disease (COPD) exacerbations. Methods: Patients with COPD presenting with acute hypercapnic respiratory failure at University Hospital Aintree between June 2006 and September 2007 and receiving NIV within 24 h of admission were studied prospectively. Random blood glucose levels were measured before NIV administration. Results: 88 patients (mean baseline pH 7.25, PaCO2 10.20 kPa, and PaO2 8.19 kPa) met the inclusion criteria, with NIV normalising arterial pH off therapy in 79 (90%). After multivariate logistic regression, the following predicted outcome: baseline respiratory rate (OR 0.91; 95% CI 0.84 to 0.99), random glucose ⩾7 mmol/l (OR 0.07; 95% CI 0.007 to 0.63) and admission APACHE II (Acute Physiology and Chronic Health Evaluation II) score (OR 0.75; 95% CI 0.62 to 0.90). The combination of baseline respiratory rate (RR) <30 breaths/min and random glucose <7 mmol/l increased prediction of NIV success to 97%, whilst use of all three factors was 100% predictive. Conclusions: In acute decompensated ventilatory failure complicating COPD, hyperglycaemia upon presentation was associated with a poor outcome. Baseline RR and hyperglycaemia are as good at predicting clinical outcomes as the APACHE II score. Combining these variables increases predictive accuracy, providing a simple method of early risk stratification.